Resin composition and method for producing the same, molded article, mechanical part, and housing

By a specific composition of resin composition, including polyphenylene ether resin, homopolystyrene and surface-treated glass fiber, the problem of mechanical properties of the existing resin composition in a hot water environment is solved, and the hot water is achieved Long-term high performance maintenance in the environment.

CN114502653BActive Publication Date: 2025-02-11ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202080070291.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-21
Filing Date
2020-10-20
Publication Date
2025-02-11
Estimated Expiration
2040-10-20

AI Technical Summary

Technical Problem

It is difficult for the existing resin composition to maintain excellent mechanical properties for a long time in a hot water environment, especially in terms of fatigue resistance and hot water resistance.

Method used

Resin compositions of specific compositions include polyphenylene ether-based resins, polyphenylene ether-based resins modified with unsaturated carboxylic acids, homopolystyrene, hydrogenated block copolymers, rubber-modified polystyrene and surface treatment The glass fibers are melt-kneaded and a resin composition with excellent mechanical properties is produced.

Benefits of technology

The resin composition that maintains tensile strength, impact strength and fatigue resistance characteristics for a long time in a hot water environment is realized, and is suitable for water supply-drainage-related mechanical components and shells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003583968200000071
    Figure BDA0003583968200000071
  • Figure BDA0003583968200000141
    Figure BDA0003583968200000141
  • Figure BDA0003583968200000142
    Figure BDA0003583968200000142
Patent Text Reader

Abstract

The present invention relates to a resin composition and a method for manufacturing the same, a molded body, a mechanical component and a housing. A resin composition comprising 20 to 50% by mass of a polyphenylene ether resin (a), 0.1 to 9% by mass of a polyphenylene ether resin (b) modified by an unsaturated carboxylic acid or its anhydride, 15 to 50% by mass of homopolystyrene (c), 1 to 25% by mass of one or more selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), and 5 to 35% by mass of surface-treated glass fiber (e); A resin composition comprising 20 to 50% by mass of a polyphenylene ether resin (a), 15 to 50% by mass of homopolystyrene (c), 5 to 35% by mass of glass fiber (e) and 0.01 to 1% by mass of a compound (f).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition and a method for producing the same, a molded body, a mechanical component, and a housing. Background Art

[0002] Polyphenylene ether resins have excellent heat resistance, hot water resistance, acid resistance, alkali resistance, etc., and have been used as mechanical parts or housings related to water supply and drainage, such as pumps, water meters, heat exchangers, water purifiers, and water softeners.

[0003] In particular, for parts and housings that require mechanical properties such as compressive strength and compressive fatigue resistance, polyphenylene ether-based resins reinforced with inorganic fillers such as glass fibers have been conventionally used.

[0004] However, in a hot water environment, the adhesive strength at the interface between the inorganic filler and the polyphenylene ether-based resin gradually decreases due to hydrolysis, resulting in a problem in that the mechanical properties of the material decrease over time.

[0005] That is, inorganic filler-reinforced polyphenylene ether resins having excellent mechanical properties such as compressive strength and compressive fatigue resistance and being able to maintain these mechanical properties at a high level for a long period of time even in a hot water environment are desired, and resin compositions such as those disclosed in Patent Documents 1 to 3 have been proposed.

[0006] Patent document 1 discloses a pump component obtained as follows for the purpose of improving hot water resistance: in a resin composition composed of a polyphenylene ether resin, an aromatic vinyl compound polymer and an aromatic vinyl compound copolymer, an inorganic filler is mixed to form a modified polyphenylene ether resin composition after replacing part or all of the polyphenylene ether resin with a modified polyphenylene ether resin modified with an unsaturated carboxylic acid or its derivatives, and a pump component is obtained therefrom.

[0007] Patent document 2 discloses the following resin composition for the purpose of improving melt fluidity or vibration fatigue characteristics: it comprises a polyphenylene ether resin having a weight average molecular weight of less than 70,000 after melt kneading, atactic homopolystyrene, a hydrogenated block copolymer comprising a polymer block mainly composed of an aromatic vinyl compound and a polymer block mainly composed of a conjugated diene compound, a compound containing functional groups such as a carboxyl group, and a surface-treated inorganic filler.

[0008] Patent Document 3 discloses a resin composition containing polyphenylene ether having a weight average molecular weight of 70,000 or more after melt kneading, polystyrene, and glass fiber for the purpose of improving hydrolysis resistance.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent No. 3966941

[0012] Patent Document 2: Japanese Patent No. 6356336

[0013] Patent Document 3: Japanese Patent No. 6170502 Summary of the invention

[0014] Problems to be solved by the invention

[0015] However, the resin composition disclosed in Patent Document 1 still has room for improvement in terms of maintaining mechanical properties in a hot water environment.

[0016] The resin composition disclosed in Patent Document 2 is excellent in mechanical properties such as vibration fatigue characteristics, but there is still room for improvement in terms of maintaining the mechanical properties in a hot water environment.

[0017] The resin composition disclosed in Patent Document 3 still has room for improvement in terms of maintaining mechanical properties in a hot water environment.

[0018] As described above, none of the resin compositions disclosed in the prior art documents can maintain these mechanical properties at a high level for a long period of time even in a hot water environment.

[0019] An object of the present invention is to provide a resin composition which is excellent in mechanical properties such as fatigue resistance and which can maintain these mechanical properties at a high level for a long period of time even in a hot water environment.

[0020] Means for solving problems

[0021] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that a resin composition having a specific composition comprising a polyphenylene ether resin (a), a polyphenylene ether resin modified with an unsaturated carboxylic acid or anhydride thereof (b), a homopolystyrene (c), at least one selected from the group consisting of a hydrogenated block copolymer (d-1) (which is a block copolymer comprising a polymer block X mainly composed of a styrene compound and a polymer block Y mainly composed of a conjugated diene compound, and a rubber-modified polystyrene (d-2), and a glass fiber (e) surface-treated with at least a silane coupling agent and an ether-based polyurethane has excellent mechanical properties such as tensile strength, impact strength, and fatigue resistance, and can maintain these mechanical properties at a high level for a long time even in a hot water environment, thereby completing the present invention.

[0022] In addition, the present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that a resin composition having a specific composition comprising a polyphenylene ether resin (a), a homopolystyrene (c), a glass fiber (e), and one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate, and hydrotalcite has excellent mechanical properties such as fatigue resistance, and that these mechanical properties can be maintained at a high level for a long time even in a hot water environment, thereby completing the present invention.

[0023] That is, the present invention is as follows. [1]

[0025] A resin composition comprising:

[0026] Polyphenylene ether resin (a) 20 to 50 mass %;

[0027] 0.1 to 9% by mass of a polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or anhydride thereof;

[0028] Homopolystyrene (c) 15 to 50 mass %;

[0029] 1 to 25% by mass of at least one selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), wherein the hydrogenated block copolymer (d-1) is obtained by hydrogenating at least a portion of a block copolymer comprising a polymer block X and a polymer block Y, wherein the polymer block X is mainly composed of a styrene-based compound and the polymer block Y is mainly composed of a conjugated diene compound; and

[0030] 5 to 35% by mass of glass fibers (e) surface-treated with at least a silane coupling agent and an ether-based polyurethane. [2]

[0032] The resin composition according to [1], wherein a molded body (surface area: Sdm 2 ) is immersed in hot water maintained at 85±2℃ (volume: Vdm 3 ), the immersion and hot water were repeatedly replaced, and the amount of butadiene monomer eluted into the hot water during the seventh immersion was less than 0.13 μg / L (where S / V ratio = 5.0 dm -1 ). [3]

[0034] The resin composition according to [1] or [2], wherein the resin composition comprises:

[0035] 0.01 to 1% by mass of one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite. [4]

[0037] The resin composition according to any one of [1] to [3], wherein the resin composition comprises:

[0038] 1 to 10,000 ppm by mass of one or more compounds selected from the group consisting of fatty acids, fatty acid esters, fatty acid metal salts and fatty acid amides (g). [5]

[0040] A molded article comprising the resin composition according to any one of [1] to [4]. [6]

[0042] A mechanical component and a housing, characterized in that they are composed of the molded body described in [5]. [7]

[0044] The mechanical component and housing as described in [6] are characterized in that they are used in contact with drinking water. [8]

[0046] A method for producing a resin composition, characterized in that the following components are melt-kneaded:

[0047] Polyphenylene ether resin (a);

[0048] A polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or an anhydride thereof;

[0049] Homopolystyrene (c);

[0050] One or more selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), wherein the hydrogenated block copolymer (d-1) is obtained by hydrogenating at least a portion of a block copolymer comprising a polymer block X and a polymer block Y, wherein the polymer block X is mainly composed of a styrene-based compound and the polymer block Y is mainly composed of a conjugated diene compound; and

[0051] Glass fibers (e) are surface-treated with at least a silane coupling agent and an ether-based polyurethane. [9]

[0053] A resin composition comprising:

[0054] Polyphenylene ether resin (a) 20 to 50% by mass,

[0055] Homopolystyrene (c) 15 to 50 mass %,

[0056] Glass fiber (e) 5-35 mass %, and

[0057] 0.01 to 1% by mass of one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite.

[10]

[0059] The resin composition as described in [9], wherein the resin composition comprises:

[0060] 1 to 25% by mass of at least one selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), wherein the hydrogenated block copolymer (d-1) is obtained by hydrogenating at least a portion of a block copolymer comprising a polymer block X and a polymer block Y, wherein the polymer block X is mainly composed of a styrene-based compound and the polymer block Y is mainly composed of a conjugated diene compound.

[11]

[0062] The resin composition according to [9] or

[10] , wherein the resin composition comprises:

[0063] Polyethylene (h) 0.1 to 5 mass %.

[12]

[0065] The resin composition according to any one of [9] to

[11] , wherein the resin composition comprises:

[0066] 1 to 10,000 ppm by mass of one or more compounds selected from the group consisting of fatty acids, fatty acid esters, fatty acid metal salts and fatty acid amides (g).

[13]

[0068] The resin composition according to any one of [9] to

[12] , wherein the glass fiber (e) is a glass fiber surface-treated with at least a silane coupling agent, an ether polyurethane and / or an ester polyurethane.

[14]

[0070] The resin composition according to any one of [9] to

[13] , wherein the resin composition comprises:

[0071] 0.1 to 9 mass % of the polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or anhydride thereof.

[15]

[0073] A molded article, characterized in that it comprises the resin composition according to any one of [9] to

[14] .

[16]

[0075] The molded article according to

[15] , wherein the molded article is immersed in hot water (volume: Vdm 3), the immersion and the hot water were repeatedly replaced, and the amount of butadiene monomer eluted into the hot water during the seventh immersion was less than 0.13 μg / L (wherein, the surface area of ​​the molded body is Sdm 2 , S / V ratio = 5.0dm -1 ),.

[17]

[0077] A mechanical component and a housing, characterized in that they are composed of the molded body described in

[15] or

[16] .

[18]

[0079] The mechanical parts and housing as described in

[17] are characterized in that they are used in contact with drinking water.

[19]

[0081] A method for producing a resin composition, characterized in that the following components are melt-kneaded:

[0082] Polyphenylene ether resin (a),

[0083] Homopolystyrene (c),

[0084] Glass fiber (e), and

[0085] One or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite.

[0086] Effects of the Invention

[0087] The resin composition of the present invention is excellent in mechanical properties such as tensile strength, impact strength, and fatigue resistance, and can maintain these mechanical properties at a high level for a long time even in a hot water environment. Its molded body can be suitably used as mechanical parts and housings related to water supply and drainage. DETAILED DESCRIPTION

[0088] Hereinafter, a specific mode for implementing the present invention (hereinafter referred to as "this embodiment") will be described in detail. The following embodiments are examples for explaining the present invention, but the present invention is not limited to the following embodiments and can be implemented with various modifications within the scope of the gist thereof.

[0089] (Resin composition)

[0090] The resin composition of one aspect of the present embodiment comprises:

[0091] Polyphenylene ether resin (a);

[0092] A polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or an anhydride thereof;

[0093] Homopolystyrene (c);

[0094] One or more selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), wherein the hydrogenated block copolymer (d-1) is obtained by hydrogenating at least a portion of a block copolymer comprising a polymer block X and a polymer block Y, wherein the polymer block X is mainly composed of a styrene-based compound and the polymer block Y is mainly composed of a conjugated diene compound; and

[0095] A glass fiber (e) surface-treated with at least a silane coupling agent and an ether-based polyurethane,

[0096] The resin composition may further contain other components.

[0097] In addition, the resin composition according to another aspect of the present embodiment comprises:

[0098] Polyphenylene ether resin (a),

[0099] Homopolystyrene (c),

[0100] Glass fiber (e), and

[0101] at least one compound (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite,

[0102] The resin composition may further contain other components.

[0103] -Polyphenylene ether resin (a)-

[0104] The polyphenylene ether resin (a) (hereinafter also referred to as component (a)) used in the present embodiment is not particularly limited, and examples thereof include a homopolymer composed of a repeating unit structure represented by the following formula (1) and / or a copolymer having a repeating unit structure represented by the following formula (1).

[0105] [Chemistry 1]

[0106]

[0107] [Where R 1 , R 2 , R 3 and R 4 Each is independently a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, a hydrocarbyloxy group, and a halogenated hydrocarbyloxy group in which a halogen atom and an oxygen atom are separated by at least two carbon atoms.]

[0108] Such polyphenylene ether resins are not particularly limited, and known resins can be used. Specific examples of polyphenylene ether resins include homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether); copolymers such as copolymers of 2,6-dimethylphenol and other phenols such as 2,3,6-trimethylphenol or 2-methyl-6-butylphenol.

[0109] As the polyphenylene ether-based resin, poly(2,6-dimethyl-1,4-phenylene ether) and a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is particularly preferred, particularly from the viewpoint of availability and various physical properties of the resin composition.

[0110] The above-mentioned polyphenylene ether-based resins may be used alone or in combination of two or more.

[0111] The polyphenylene ether-based resin can be produced by a known method.

[0112] The method for producing the polyphenylene ether resin is not particularly limited, and examples thereof include: a method for oxidative polymerization of 2,6-xylenol using a mixture of a cuprous salt and an amine as a catalyst as described in U.S. Pat. No. 3,306,874 of Hay; and other methods described in U.S. Pat. No. 3,306,875, U.S. Pat. No. 3,257,357, U.S. Pat. No. 3,257,358, Japanese Patent Publication No. 52-17880, Japanese Patent Application Publication No. 50-51197, and Japanese Patent Application Publication No. 63-152628.

[0113] From the perspective of setting the weight average molecular weight of component (a) in the stage after forming the resin composition (stage after melt kneading) to the range described below, the lower limit of the weight average molecular weight of component (a) in the stage of raw materials (stage before melt kneading) is preferably 30,000 or more, more preferably 35,000 or more, and particularly preferably 40,000 or more, and the upper limit is preferably 80,000 or less, more preferably 75,000 or less, and particularly preferably 55,000 or less.

[0114] From the perspective of improving the fatigue resistance of the resin composition, the weight average molecular weight of component (a) in the stage after forming the resin composition (the stage after melt kneading) is preferably 35,000 or more, more preferably 40,000 or more, and particularly preferably 45,000 or more. From the perspective of improving the melt fluidity of the resin composition, it is preferably 95,000 or less, more preferably 90,000 or less, and particularly preferably 70,000 or less.

[0115] In addition, the weight average molecular weight can be determined by a conventionally known method using gel permeation chromatography (mobile layer: chloroform, standard substance: polystyrene).

[0116] From the perspective of improving the heat resistance and fatigue resistance of the resin composition, the content of component (a) is 20% by mass or more, preferably 25% by mass or more, and more preferably 30% by mass or more, relative to 100% by mass of the resin composition. In addition, from the perspective of improving the melt fluidity of the resin composition, the content of component (a) is 50% by mass or less, preferably 45% by mass or less, and more preferably 40% by mass or less.

[0117] -Polyphenylene ether resin modified with unsaturated carboxylic acid or its anhydride (b)-

[0118] The resin composition of the present embodiment may include a polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or an anhydride thereof (hereinafter also referred to as component (b)). The polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or anhydride thereof (hereinafter also referred to as component (b)) used in the present embodiment is a resin to which an unsaturated carboxylic acid or anhydride thereof is covalently bonded to a side chain or terminal of the polyphenylene ether resin.

[0119] The polyphenylene ether resin used in the component (b) is not particularly limited, and examples thereof include a homopolymer composed of the repeating unit structure represented by the above-mentioned formula (1) and / or a copolymer having the repeating unit structure represented by the formula (1).

[0120] Specific examples include homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether); copolymers such as copolymers of 2,6-dimethylphenol and other phenols such as 2,3,6-trimethylphenol or 2-methyl-6-butylphenol; in particular, from the perspective of availability, copolymers of poly(2,6-dimethyl-1,4-phenylene ether) and 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is particularly preferred.

[0121] These may be used alone or in combination of two or more.

[0122] The unsaturated carboxylic acid or its anhydride used in the component (b) is not particularly limited, and for example, unsaturated monocarboxylic acids such as acrylic acid and methacrylic acid can be cited; unsaturated di(tri)carboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, itaconic acid, glutaconic acid, aconitic acid, muconic acid, and 4-cyclohexene-1,2-dicarboxylic acid; and anhydrides of unsaturated di(tri)carboxylic acids such as maleic anhydride, citraconic anhydride, itaconic anhydride, glutaconic anhydride, aconitic anhydride, and 4-cyclohexene-1,2-dicarboxylic anhydride. In particular, maleic acid and maleic anhydride are preferred from the perspective of ease of modification and ease of availability. These can be used alone or in combination of two or more.

[0123] As described later, component (b) is bonded to the surface of the glass fiber via a silane coupling agent, thereby increasing the bonding strength at the interface between the glass fiber and the polyphenylene ether resin (a), thereby increasing the mechanical properties of the resin composition, such as tensile strength, impact strength, and fatigue resistance, while also increasing the retention of these mechanical properties in a hot water environment (hereinafter also referred to as "hot water resistance").

[0124] The modification rate of the unsaturated carboxylic acid or its anhydride of the component (b) (the amount (percentage) of the unsaturated carboxylic acid or its anhydride added per 100% by mass of the polyphenylene ether resin constituting the component (b)) is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 0.3% by mass or more, from the viewpoint of improving the tensile strength, impact strength, fatigue resistance and hot water resistance of the resin composition. Furthermore, from the viewpoint of improving the hot water resistance of the resin composition, it is preferably 1.5% by mass or less, more preferably 1% by mass or less, and particularly preferably 0.8% by mass or less.

[0125] The modification rate of the unsaturated carboxylic acid or its anhydride of the component (b) can be determined using a potentiometric titration method, a nuclear magnetic resonance apparatus (NMR), or the like.

[0126] From the perspective of improving the tensile strength, impact strength, fatigue resistance and hot water resistance of the resin composition, the content of component (b) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and particularly preferably 1% by mass or more, relative to 100% by mass of the resin composition. From the perspective of improving the hot water resistance of the resin composition, it is preferably 9% by mass or less, more preferably 6% by mass or less, and particularly preferably 3% by mass or less.

[0127] The component (b) can be produced by, for example, melt-kneading a polyphenylene ether-based resin and an unsaturated carboxylic acid or anhydride thereof using a single-screw extruder or a twin-screw extruder.

[0128] In the present embodiment, the composition obtained by the above-mentioned melt-kneading can be used as the component (b) as it is.

[0129] When producing the component (b), an organic peroxide such as hydroperoxides, dialkyl peroxides, or diacyl peroxides may be appropriately added as a radical reaction initiator.

[0130] In addition, in addition to the polyphenylene ether resin, unsaturated carboxylic acid or its anhydride, resins such as homopolystyrene, rubber-modified polystyrene and hydrogenated block copolymers may also coexist. The above-mentioned hydrogenated block copolymer is a block copolymer comprising a polymer block mainly composed of a styrene compound and a polymer block mainly composed of a conjugated diene compound, at least a portion of which is hydrogenated.

[0131] However, when the polyphenylene ether resin (a) and the unsaturated carboxylic acid or its anhydride are melt-kneaded at the stage of forming the resin composition of the present embodiment (the stage of melt-kneading), it is difficult to obtain desired hot water resistance.

[0132] -Homopolystyrene (c)-

[0133] The homopolystyrene (c) (hereinafter also referred to as component (c)) used in the present embodiment is not particularly limited, and examples thereof include homopolymers of styrene compounds having stereoregularity selected from atactic, syndiotactic, and isotactic, or copolymers of two or more styrene compounds.

[0134] These may be used alone or in combination of two or more.

[0135] Examples of the styrene-based compound include styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4,6-trimethylstyrene, and 4-tert-butylstyrene. In particular, atactic homopolystyrene is preferred from the viewpoint of easy availability.

[0136] From the perspective of improving the melt fluidity of the resin composition, the content of component (c) is 15% by mass or more, preferably 20% by mass or more, and more preferably 25% by mass or more, relative to 100% by mass of the resin composition. In addition, from the perspective of improving the heat resistance and fatigue resistance of the resin composition, the content of component (c) is 50% by mass or less, preferably 45% by mass or less, and more preferably 40% by mass or less.

[0137] -Hydrogenated block copolymer (d-1)-

[0138] The resin composition of the present embodiment may include a hydrogenated block copolymer (d-1) (hereinafter also referred to as component (d-1)), wherein at least a portion of a block copolymer including a polymer block X mainly composed of a styrene-based compound and a polymer block Y mainly composed of a conjugated diene compound is hydrogenated. Component (d-1) imparts impact strength to the resin composition of the present embodiment.

[0139] The block structure of the component (d-1) is not particularly limited. For example, when "X" represents polymer block X and "Y" represents polymer block Y, structures such as XY, XYX, XYXY, XYXYX, and (XY-)4Si may be mentioned.

[0140] --Polymer Block X--

[0141] The polymer block X mainly composed of a styrene-based compound is not particularly limited, and examples thereof include a homopolymer block of a styrene-based compound and a copolymer block of a styrene-based compound and a conjugated diene compound.

[0142] The phrase “mainly composed of a styrene-based compound” in the polymer block X means that the content of the polymer portion of the styrene-based compound in the polymer block X is 50 to 100% by mass, preferably 70 to 100% by mass.

[0143] There are no particular limitations on the styrene compounds constituting the polymer block X, and examples thereof include styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4,6-trimethylstyrene, and 4-tert-butylstyrene, preferably styrene. The styrene compounds may be used alone or in combination of two or more.

[0144] --Polymer Block Y--

[0145] The polymer block Y mainly composed of a conjugated diene compound is not particularly limited, and examples thereof include a homopolymer block of a conjugated diene compound and a copolymer block of a conjugated diene compound and a styrene-based compound.

[0146] It should be noted that the phrase “mainly composed of a conjugated diene compound” in the polymer block Y means that the content of the polymer portion of the conjugated diene compound in the polymer block Y is 50 to 100% by mass, preferably 70 to 100% by mass.

[0147] The conjugated diene compound constituting the polymer block Y is not particularly limited, and examples thereof include 1,3-butadiene, 1,3-pentadiene, isoprene, and 2,3-dimethyl-1,3-butadiene, preferably 1,3-butadiene and isoprene. These may be used alone or in combination of two or more.

[0148] There is no particular limitation on the bonding pattern of the conjugated diene compound, and it can be selected arbitrarily. From the perspective of improving the heat resistance of the resin composition, the vinyl bonding amount (the ratio of the 1,2-bonding pattern, 3,4-bonding pattern and 1,4-bonding pattern of the conjugated diene compound included through the 1,2-bonding pattern and the 3,4-bonding pattern) is preferably 2% to 90%. For example, when the conjugated diene compound is mainly composed of 1,3-butadiene, the vinyl bonding amount is preferably 30 to 90%, and when it is mainly composed of isoprene, the vinyl bonding amount is preferably 2 to 80%.

[0149] In addition, the vinyl bond amount can be obtained using a nuclear magnetic resonance apparatus (NMR).

[0150] The molecular structure of the component (d-1) is not particularly limited, and examples thereof include linear, branched, radial, and combinations thereof.

[0151] The distribution of the styrene compound in the molecular chain of the polymer block X and the conjugated diene compound in the molecular chain of the polymer block Y is not particularly limited, and examples thereof include random, tapered, partial block, and combinations thereof.

[0152] When the component (d-1) contains two or more polymer blocks X or two or more polymer blocks Y, the two or more polymer blocks X or two or more polymer blocks Y may have the same structure or different structures.

[0153] From the perspective of improving the dispersibility of component (d-1) in components (a), (b) and (c), the proportion of the polymer portion of the styrene-based compound in component (d-1) is preferably 20% by mass or more, more preferably 30% by mass or more, and from the perspective of improving the impact strength of the resin composition, it is preferably 95% by mass or less, more preferably 80% by mass or less.

[0154] The ratio of the polymer portion of the styrene compound in the component (d-1) can be measured and calculated using an ultraviolet spectrophotometer or a nuclear magnetic resonance apparatus (NMR).

[0155] There are no particular limitations on the method for hydrogenating the block copolymer, and examples thereof include: (1) a supported heterogeneous hydrogenation catalyst in which a metal such as Ni, Pt, Pd, or Ru is supported on carbon, silicon oxide, alumina, diatomaceous earth, or the like; (2) a so-called Ziegler-type hydrogenation catalyst in which an organic acid salt or a transition metal salt such as acetylacetonate of Ni, Co, Fe, or Cr and a reducing agent such as an organic aluminum; (3) a homogeneous hydrogenation catalyst such as an organic metal complex of Ti, Ru, Rh, or Zr, and the like is used to carry out hydrogenation under conditions such as a reaction temperature of 0 to 200° C. and a hydrogen pressure of 0.1 to 15 MPa.

[0156] By the above hydrogenation, the double bonds of the aliphatic chains derived from the polymer portion of the conjugated diene compound which may be contained in the polymer block X and the polymer portion of the conjugated diene compound contained in the polymer block Y are reduced.

[0157] From the perspective of improving the heat resistance and impact strength of the resin composition, the hydrogenation rate of component (d-1) is preferably 50% or more, more preferably 90% or more, and particularly preferably 95% or more, relative to the total amount of fatty chain double bonds in the polymer portion derived from the conjugated diene compound.

[0158] The hydrogenation rate of the component (d-1) can be measured and calculated using an infrared spectrophotometer or a nuclear magnetic resonance apparatus (NMR).

[0159] From the perspective of improving the impact strength of the resin composition, the weight average molecular weight of the component (d-1) is preferably 50,000 or more, more preferably 100,000 or more, and further preferably 150,000 or more. From the perspective of improving the melt fluidity of the resin composition, it is preferably 300,000 or less.

[0160] In addition, the weight average molecular weight can be determined by a conventionally known method using gel permeation chromatography (mobile layer: chloroform, standard substance: polystyrene).

[0161] From the perspective of improving the impact strength of the resin composition, the content of the component (d-1) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and particularly preferably 1% by mass or more, relative to 100% by mass of the resin composition. From the perspective of improving the fatigue resistance of the resin composition, the content is preferably 25% by mass or less, more preferably 15% by mass or less, and particularly preferably 5% by mass or less.

[0162] -Rubber modified polystyrene (d-2)-

[0163] The resin composition of the present embodiment may contain rubber-modified polystyrene (d-2) (hereinafter, also simply referred to as component (d-2)). The component (d-2) imparts impact strength to the resin composition of the present embodiment.

[0164] The component (d-2) is a copolymer obtained by polymerizing a styrene compound in the presence of a rubber polymer.

[0165] Examples of the styrene-based compound include styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4,6-trimethylstyrene, and 4-tert-butylstyrene, and styrene is preferred.

[0166] In addition, as the compound copolymerizable with the above-mentioned styrene-based compound, for example, (meth)acrylates such as ethyl acrylate and methyl methacrylate; unsaturated nitrile compounds such as acrylonitrile and methacrylonitrile; acid anhydrides such as maleic anhydride, etc. can be used together with the above-mentioned styrene-based compound. The content of these compounds copolymerizable with the styrene-based compound is preferably 20% by mass or less, and more preferably 15% by mass or less, relative to the total amount of the styrene-based compound and the compound.

[0167] As the rubber polymer, for example, conjugated diene rubbers such as polybutadiene and polyisoprene, copolymers of conjugated diene compounds and styrene compounds, ethylene-propylene copolymer rubbers, etc. can be cited, preferably copolymers of polybutadiene and styrene compounds. These can also be hydrogenated to reduce a part of the double bonds of the fatty chains in the rubber polymer.

[0168] The content of the rubber polymer in the component (d-2) is not particularly limited, but is preferably 3% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 15% by mass or less.

[0169] From the perspective of improving the impact strength of the resin composition, the content of component (d-2) is preferably 0.1% by mass or more, more preferably 1% by mass or more, and particularly preferably 5% by mass or more, relative to 100% by mass of the resin composition. From the perspective of improving the fatigue resistance of the resin composition, it is preferably 25% by mass or less, more preferably 20% by mass or less, and particularly preferably 15% by mass or less.

[0170] -Glass fiber(e)-

[0171] The resin composition of the present embodiment contains glass fiber (e) (hereinafter, also simply referred to as component (e)).

[0172] The glass composition of the glass fiber used as the component (e) is not particularly limited, and examples thereof include E glass, S glass, ARG glass, D glass, C glass, etc., preferably E glass. The diameter of the glass fiber is not particularly limited, but is preferably 5 μm to 25 μm, more preferably 10 μm to 15 μm.

[0173] The glass fiber used as the component (e) is preferably a glass fiber surface-treated with at least a silane coupling agent and an ether-based polyurethane and / or an ester-based polyurethane from the viewpoint described below.

[0174] The alkoxysilyl group of the silane coupling agent reacts with the silanol group present on the surface of the glass fiber to form a siloxane bond. On the other hand, the organic functional group of the silane coupling agent reacts with the amino group or unreacted hydroxyl group from the polymerization process that may remain in the polyphenylene ether resin (a), and the functional groups such as the carboxyl group of the polyphenylene ether resin (b) modified with unsaturated carboxylic acid or its anhydride to form a covalent bond. In this way, the silane coupling agent improves the bonding strength of the interface between the glass fiber and the resin matrix containing the polyphenylene ether resin, and improves the mechanical properties such as tensile strength, impact strength, fatigue resistance of the resin composition, and improves hot water resistance.

[0175] The silane coupling agent that can be used as component (e) is not particularly limited, and examples thereof include aminosilanes such as 3-aminopropyltrialkoxysilane, N-2-(aminoethyl)-3-aminopropyltrialkoxysilane, and N-2-(aminoethyl)-8-aminooctyltrialkoxysilane; epoxysilanes such as 3-glycidoxypropyltrialkoxysilane, 8-glycidoxyoctyltrialkoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrialkoxysilane; isocyanatesilanes such as 3-isocyanatepropyltrialkoxysilane, etc., preferably aminosilanes or epoxysilanes, and particularly preferably aminosilanes. These may be used alone or in combination of two or more.

[0176] Furthermore, by surface treatment with ether polyurethane and / or ester polyurethane, the dispersion of glass fiber in the resin matrix containing polyphenylene ether resin is good, and the mechanical properties such as tensile strength, impact strength, and fatigue resistance of the resin composition are improved. Ether polyurethane has basically no water absorption and is difficult to hydrolyze, so it is more preferred from the perspective of improving the hot water resistance of the resin composition.

[0177] The ether polyurethane that can be used as the component (e) is not particularly limited, and examples thereof include ether polyurethanes prepared using as main components at least one selected from polyisocyanates such as hexamethylene diisocyanate, toluene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate; and at least one selected from polyether polyols having a repeating unit structure represented by the following formula (2) and / or a repeating unit structure represented by the following formula (3).

[0178] [Chemistry 2]

[0179]

[0180] [Chemistry 3]

[0181]

[0182] [In the formula, m is 1 or 2, and n is an integer from 2 to 5.]

[0183] The ester polyurethane that can be used as the component (e) is not particularly limited. For example, there can be mentioned ester polyurethanes produced by polycondensing one or more selected from polyester polyols as main components, wherein the polyester polyols are obtained by polycondensing one or more selected from polyisocyanates such as hexamethylene diisocyanate, toluene diisocyanate, xylylenediisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate; one or more selected from dicarboxylic acids such as adipic acid, phthalic acid, isophthalic acid, and terephthalic acid; and one or more selected from polyols such as ethylene glycol, 1,3-propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, and tripropylene glycol.

[0184] The component (e) may contain, as a surface treatment agent, styrene-maleic anhydride copolymer, olefin-maleic anhydride copolymer, antioxidant, nonionic surfactant, ionic surfactant, plasticizer, etc., in addition to the above-mentioned silane coupling, ether polyurethane, and ester polyurethane.

[0185] From the perspective of improving the heat resistance, tensile strength and fatigue resistance of the resin composition, the content of component (e) is 5% by mass or more, preferably 7% by mass or more, and more preferably 10% by mass or more, relative to 100% by mass of the resin composition. In addition, from the perspective of improving the melt fluidity and hot water resistance of the resin composition, the content of component (e) is 35% by mass or less, preferably 30% by mass or less, and more preferably 28% by mass or less.

[0186] -Compound (f)-

[0187] The resin composition of the present embodiment may contain one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite (hereinafter also referred to as component (f)). Component (f) further improves the hot water resistance of the resin composition.

[0188] The hydrotalcite is not particularly limited, and examples thereof include a hydrotalcite compound represented by the following formula (4) and a calcined product thereof.

[0189] [Chemistry 4]

[0190] (M 2+ ) 1-x (M 3+ ) x (OH)2(A n- ) x / n ·mH2O···(4)

[0191] [Wherein, M 2+ Represents Mg 2+ , Zn 2+ Divalent metal ions, M 3+ Al 3+ , Fe 3+ A trivalent metal ion. n- Represents Cl - 、CO3 2- 、SO4 2- Anions with equal valence n. x, m, and n satisfy 0 <x<0.5、1≦n≦4、m≧0。]

[0192] From the perspective of improving the hot water resistance of the resin composition, the content of the component (f) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more, relative to 100% by mass of the resin composition. From the perspective of improving the fatigue resistance of the resin composition, it is preferably 1% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.2% by mass or less.

[0193] -Compound (g)-

[0194] The resin composition of this embodiment may contain one or more compounds (g) selected from the group consisting of fatty acids, fatty acid esters, fatty acid metal salts and fatty acid amides (hereinafter also referred to as component (g)). Component (g) improves mold releasability of the resin composition during molding.

[0195] (g) The component is selected from fatty acids such as palmitic acid, stearic acid, behenic acid, and erucic acid; fatty acid esters such as glyceryl monostearate and glyceryl distearate; fatty acid metal salts such as magnesium palmitate, calcium palmitate, zinc palmitate, magnesium stearate, calcium stearate, and zinc stearate; and fatty acid amides such as palmitamide, stearamide, behenamide, erucamide, methylene bis stearamide, and ethylene bis stearamide. These may be used alone or in combination of two or more.

[0196] From the perspective of improving the mold releasability of the resin composition during molding, the content of component (g) is preferably 1 mass ppm or more, more preferably 10 mass ppm or more, and particularly preferably 100 mass ppm or more, relative to 100 mass ppm of the resin composition. In addition, from the perspective of improving the hot water resistance of the resin composition, it is preferably 10,000 mass ppm or less, more preferably 3,000 mass ppm or less, and particularly preferably 1,000 mass ppm or less.

[0197] The component (g) may be added at the stage of forming the resin composition (during melt kneading), or may be spread on the surface of the resin composition which is usually in the form of pellets at a stage after the resin composition is formed (stage after melt kneading).

[0198] -Polyethylene(h)-

[0199] The resin composition of the present embodiment may contain polyethylene (h) (hereinafter, also referred to simply as component (h)). The component (h) improves mold releasability of the resin composition during molding.

[0200] The component (h) is not particularly limited, but may be selected from high-density polyethylene (density 940 to 970 kg / m 3 ), low-density polyethylene (density 910~940kg / m 3 ), linear low-density polyethylene (density 900-940kg / m 3 These may be used alone or in combination of two or more.

[0201] Regarding the melt fluidity of the component (h), from the perspective of improving the mold releasability of the resin composition during molding, the melt flow rate measured at a temperature of 190°C and a load of 2.16 kg in accordance with ISO1133 is preferably 10 g / 10 minutes or more, more preferably 15 g / 10 minutes or more. In addition, from the perspective of improving the heat resistance of the resin composition, it is preferably 65 g / 10 minutes or less, more preferably 60 g / 10 minutes or less.

[0202] From the perspective of improving the mold releasability of the resin composition during molding, the content of the component (h) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and particularly preferably 1% by mass or more, relative to 100% by mass of the resin composition. From the perspective of improving the heat resistance of the resin composition, it is preferably 5% by mass or less, more preferably 3% by mass or less, and particularly preferably 2% by mass or less.

[0203] -Other ingredients-

[0204] The resin composition of the present embodiment may contain other components as needed, in addition to the above-mentioned components (a) to (c), component (d-1), component (d-2), and components (e) to (h), within a range that does not impair the tensile strength, impact strength, fatigue resistance, hot water resistance, etc. of the resin composition of the present embodiment.

[0205] As other components, for example, thermoplastic resins other than components (a) to (c), component (d-1), component (d-2), and component (h), antioxidants, UVA, HALS, metal deactivators, flame retardants, plasticizers, inorganic fillers other than component (e), organic fillers, colorants, etc. can be mentioned, but it is not limited to these.

[0206] Regarding the resin composition of the present embodiment, as thermoplastic resins other than components (a) to (c), component (d-1), component (d-2), and component (h), for example, polyolefin resins such as polypropylene and polybutene; polyolefin copolymers such as ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-octene copolymers, ethylene-ethyl acrylate copolymers, and ethylene-ethyl methacrylate copolymers, etc., can be cited. From the perspective of improving the fatigue resistance and hot water resistance of the resin composition, the total content of the thermoplastic resins other than components (a) to (c), component (d-1), component (d-2), and component (h) is preferably 5% by mass or less, more preferably 3% by mass or less, and particularly preferably 2% by mass or less, relative to 100% by mass of the resin composition.

[0207] The resin composition of the present embodiment may contain, as a flame retardant, monophosphates such as triphenyl phosphate, tricresyl phosphate, and tricresyl phosphate; condensed phosphates such as resorcinol bis(diphenyl phosphate), resorcinol bis(diphenyl phosphate), and bisphenol A bis(diphenyl phosphate); and one or more thereof. From the perspective of improving the hot water resistance of the resin composition, the content thereof is preferably 13% by mass or less, more preferably 8% by mass or less, and particularly preferably 3% by mass or less, relative to 100% by mass of the resin composition.

[0208] The resin composition of the present embodiment may contain, as an inorganic filler, one or more of glass fibers, glass flakes, talc, mica, wollastonite, etc. other than component (e). From the perspective of improving the hot water resistance of the resin composition, the content thereof is preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less, relative to 100% by mass of the resin composition.

[0209] (Method for producing resin composition)

[0210] The resin composition of one aspect of the present embodiment can be produced by melt-kneading the above-mentioned polyphenylene ether resin (a), the polyphenylene ether resin modified with an unsaturated carboxylic acid or anhydride thereof (b), homopolystyrene (c), one or more selected from the group consisting of a hydrogenated block copolymer (d-1) (which is a block copolymer comprising a polymer block X mainly composed of a styrene compound and a polymer block Y mainly composed of a conjugated diene compound, and hydrogenated), and a rubber-modified polystyrene (d-2), a glass fiber (e) surface-treated with at least a silane coupling agent and an ether-based polyurethane, and optional other components.

[0211] The resin composition of another aspect of the present embodiment can be produced by melt-kneading the above-mentioned polyphenylene ether resin (a), homopolystyrene (c), glass fiber (e), one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite, and any other optional components.

[0212] An example of a preferred method for producing the resin composition of the present embodiment is:

[0213] (1) A method for producing a resin composition having a pellet shape by simultaneously melt-kneading components (a) to (c) as resin components and one or more selected from the group consisting of components (d-1) and (d-2), and then adding component (e) as an inorganic filler and further melt-kneading, thereby obtaining a resin composition having a pellet shape;

[0214] (2) A method for producing a resin composition having a pellet shape by simultaneously melt-kneading components (a) to (c) as resin components, one or more selected from the group consisting of components (d-1) and (d-2), and component (e) as an inorganic filler;

[0215] (3) A method for producing a resin composition having a pellet shape by simultaneously melt-kneading components (a) to (c) as resin components and one or more selected from the group consisting of components (d-1) and (d-2) to obtain a resin composition having a pellet shape, then melt-kneading the pellets again, and then adding component (e) as an inorganic filler and further melt-kneading to obtain a resin composition having a pellet shape;

[0216] etc.

[0217] Another example of a preferred method for producing the resin composition of the present embodiment includes:

[0218] (1) A method for producing a resin composition having a pellet shape by simultaneously melt-kneading components (a) and (c) as resin components and any other components, and then adding component (e) as an inorganic filler and further melt-kneading the mixture;

[0219] (2) A method for producing a resin composition having a pellet shape by simultaneously melt-kneading components (a) and (c) as resin components, any other components, and component (e) as an inorganic filler;

[0220] (3) A method for producing a resin composition in the form of pellets by simultaneously melt-kneading the components (a) and (c) as resin components and any other components, and then melt-kneading the pellets again, and then adding the component (e) as an inorganic filler and further melt-kneading to obtain a resin composition in the form of pellets;

[0221] etc.

[0222] Examples of an apparatus preferably used for melt-kneading the components include a multi-screw extruder such as a single-screw extruder or a twin-screw extruder, a roll, a kneader, a Banbury mixer, and the like. In the present embodiment, a multi-screw extruder is particularly preferred.

[0223] More specifically, it is preferred that the multi-screw extruder has a first raw material supply port, a first vacuum exhaust port, a supply port after the second raw material supply port, and a second vacuum exhaust port in order from the upstream side along the raw material flow direction. Furthermore, it is preferred that a kneading section is provided between the first raw material supply port and the first vacuum exhaust port, and between the supply port after the second raw material supply port and the second vacuum exhaust port.

[0224] In a particularly preferred method for manufacturing the resin composition of the present embodiment, components (a) to (c) as resin components, any other components, and one or more selected from the group consisting of components (d-1) and (d-2) can be supplied from the first raw material supply port, and then component (e) as an inorganic filler can be added from the second raw material supply port.

[0225] In a particularly preferred method for producing the resin composition of the present embodiment, components (a) and (c) as resin components and any other components may be supplied from the first raw material supply port, and then component (e) as an inorganic filler may be added from the second raw material supply port.

[0226] The amount of each component added in the method for producing the resin composition of the present embodiment can be set to the content of each component in the resin composition of the present embodiment described above.

[0227] When the components are melt-kneaded, the melt-kneading temperature is not particularly limited, and can usually be set to 200 to 350°C. The screw speed is not particularly limited, and can usually be set to 100 to 1200 rpm. The discharge amount is not particularly limited, and can usually be set to 10 to 1200 kg / hour. The vacuum degree is not particularly limited, and can usually be set to -0.06 to -0.099 MPa.

[0228] (molded bodies, mechanical parts and housings)

[0229] By molding the resin composition of the present embodiment, a molded body composed of the resin composition of the present embodiment can be obtained.

[0230] The molding method of the resin composition is not particularly limited, and examples thereof include injection molding, in-mold molding, insert molding, extrusion molding, sheet molding, film molding, hot press molding, rotational molding, and lamination molding.

[0231] -Amount of butadiene monomer eluted from the molded article into hot water-

[0232] Incidentally, the German standard KTW concerning parts for use in contact with drinking water has an upper limit on the concentration of butadiene monomer that is eluted into hot water when the final product is immersed in hot water as one of the requirements of the standard.

[0233] Regarding the resin composition of the present embodiment, from the viewpoint of adaptability to KTW, it is preferred that a molded article (surface area: Sdm 2 ) is immersed in hot water maintained at 85±2℃ (volume: Vdm 3), the immersion and hot water were repeatedly replaced, and the amount of butadiene monomer eluted into the hot water during the seventh immersion was less than 0.13 μg / L (where S / V ratio = 5.0 dm -1 ).

[0234] More specifically, a molded body (surface area: Sdm 2 ), a dissolution test of butadiene monomer from a molded body into hot water was carried out according to the following steps;

[0235] [0] Pre-cleaning

[0236] The molded body rinsed with tap water for 1 hour was immersed in hot water maintained at 85±2° C. for 24 hours, and then further rinsed with tap water for 1 hour.

[0237] [1] Immersion test

[0238] The molded body pre-cleaned in [0] was placed in hot water (volume: Vdm 3 ) for 24 hours (first immersion). Replace the hot water and continue to immerse in hot water (volume: Vdm 3 ) for 24 hours (second immersion). Replace the hot water and continue to immerse in hot water (volume: Vdm 3 ) for 24 hours (third immersion). Replace the hot water and continue to immerse in hot water (volume: Vdm 3 ) for 72 hours (the fourth immersion). The same operation was repeated three times to replace the hot water and immerse in the hot water for 24 hours (the fifth to seventh immersions).

[0239] [2] Determination of the amount of butadiene monomer dissolved

[0240] The butadiene monomer concentration of the hot water obtained in the seventh immersion in the above [1] was measured using purge & trap GC / MS as the elution amount of butadiene monomer (unit: μg / L).

[0241] The double bonds of the fatty chains contained in the component (d-1) and the double bonds of the fatty chains contained in the component (d-2) may be thermally decomposed under high temperature conditions. In particular, when the components (d-1) and (d-2) have polybutadiene moieties, the polybutadiene moieties may be thermally decomposed at the stage of forming the resin composition (the stage of melt kneading), and the obtained resin composition may be a composition containing butadiene monomers.

[0242] Therefore, from the perspective of setting the amount of butadiene monomer eluted from the molded article into hot water to the above range, the content of the polybutadiene portion derived from the components (d-1) and (d-2) relative to 100% by mass of the resin composition is preferably 2.0% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.50% by mass or less.

[0243] The molded article composed of the resin composition of the present embodiment is suitably used as a water supply-drainage related mechanical part and housing, such as a pump housing, a valve, a piping assembly, a flange, a water meter, a heat exchanger, a water purifier, a water softener, a shower head, etc. It is particularly suitably used as a water supply-drainage related mechanical part and housing that is used in contact with drinking water.

[0244] Example

[0245] Hereinafter, the present invention will be described with reference to specific Examples and Comparative Examples, but the present invention is not limited to these.

[0246] The raw materials used for the resin compositions of the Examples and Comparative Examples described below are as follows.

[0247] -Polyphenylene ether resin (a)-

[0248] (a-1) Poly(2,6-dimethyl-1,4-phenylene ether) (weight average molecular weight: 52000)

[0249] (a-2) Poly(2,6-dimethyl-1,4-phenylene ether) (weight average molecular weight: 74000)

[0250] -Polyphenylene ether resin modified with unsaturated carboxylic acid or its anhydride (b)-

[0251] (b-1)

[0252] A modified polyphenylene ether obtained by melt-kneading 100 parts by mass of poly(2,6-dimethyl-1,4-phenylene ether) (weight average molecular weight: 52,000) and 2.5 parts by mass of maleic anhydride at 320° C. in a nitrogen atmosphere. The modification rate of maleic anhydride was 0.6% by mass.

[0253] (b-2)

[0254] A modified polyphenylene ether obtained by melt-kneading 100 parts by mass of poly(2,6-dimethyl-1,4-phenylene ether) (weight average molecular weight: 52000) and 0.8 parts by mass of maleic anhydride at 320° C. in a nitrogen atmosphere. The modification rate of maleic anhydride was 0.2% by mass.

[0255] (b-3)

[0256] Modified polyphenylene ether was obtained by melt-kneading 100 parts by mass of poly(2,6-dimethyl-1,4-phenylene ether) (weight average molecular weight: 52,000), 2.5 parts by mass of maleic anhydride and 0.5 parts by mass of dicumyl peroxide at 320° C. in a nitrogen atmosphere. The modification rate of maleic anhydride was 1.2% by mass.

[0257] -Homopolystyrene (c)-

[0258] (c-1) Atactic homopolystyrene (trade name: polystyrene 685, manufactured by PS Japan)

[0259] -Hydrogenated block copolymer (d-1)-

[0260] (d-1-1)

[0261] "Polystyrene-hydrogenated polybutadiene-polystyrene" triblock copolymer (vinyl bond content: 38%, styrene content: 33% by mass, weight average molecular weight: 250,000, hydrogenation rate for the polybutadiene part: 99.8%)

[0262] (d-1-2)

[0263] "Polystyrene-hydrogenated polybutadiene-polystyrene-hydrogenated polybutadiene" tetrablock copolymer (vinyl bond content: 38%, styrene content: 60% by mass, weight average molecular weight: 110,000, hydrogenation rate of the polybutadiene portion: 99.8%)

[0264] -Rubber modified polystyrene (d-2)-

[0265] (d-2) Rubber-modified polystyrene containing 8% by mass of polybutadiene rubber

[0266] -Surface treated glass fiber (e)-

[0267] (e-1)

[0268] Glass fiber (average diameter: 13 μm) surface-treated with 3-aminopropyltriethoxysilane and ether polyurethane (formed from polyether polyol having isophorone diisocyanate and ethylene oxide as repeating unit structures as main components)

[0269] (e-2)

[0270] Glass fiber (average diameter: 10 μm) surface-treated with 3-aminopropyltriethoxysilane and ether polyurethane (formed from polyether polyol having dicyclohexylmethane diisocyanate and propylene oxide as repeating unit structures as main components)

[0271] (e-3)

[0272] Glass fiber (average diameter: 13 μm) surface treated with 3-aminopropyltriethoxysilane and ester polyurethane (formed mainly from a condensation product of isophorone diisocyanate and adipic acid and ethylene glycol)

[0273] (e-4)

[0274] Glass fiber surface treated with 3-aminopropyltriethoxysilane (average diameter: 13 μm)

[0275] -Compound (f)-

[0276] (f-1) Magnesium oxide (trade name: KYOWAMAG150, manufactured by Kyowa Chemical Industry)

[0277] (f-2) Hydrotalcite Mg 4.5 Al2(OH) 13 (CO3) · 3.5H2O (Trade name: DHT-4C, manufactured by Kyowa Chemical Industry)

[0278] -Compound (g)-

[0279] (g-1) Ethylene bisstearamide

[0280] (g-2) Magnesium Stearate

[0281] -Compound (h)-

[0282] (h-1) Low-density polyethylene (density: 919kg / m 3 , melt flow rate (190°C, 2.16kg): 22g / 10min)

[0283] -Other ingredients-

[0284] (x-1) Antioxidant (trade name: Irganox 565, manufactured by BASF)

[0285] (x-2) Antioxidant (trade name: Irgafos 168, manufactured by BASF)

[0286] (x-3)Maleic anhydride

[0287] The methods (1) to (8) for measuring the physical properties of the resin compositions of the Examples and Comparative Examples described below are as follows.

[0288] (1) Melt fluidity

[0289] Pellets of the resin compositions of Examples and Comparative Examples described below were pre-dried at 80°C for 2 hours and then measured for melt mass flow rate (MFR) (unit: g / 10 min) at 250°C and a load of 10 kg in accordance with JIS K7210-1.

[0290] As an evaluation standard, it was determined that the higher the measured value, the better the melt fluidity.

[0291] (2) Heat resistance

[0292] The pellets of the resin compositions of the examples and comparative examples described below were pre-dried at 80°C for 2 hours and then fed to a coaxial screw injection molding machine (model: IS-100GN, manufactured by TOSHIBA MACHINE) set at 220-320°C, and molded into JIS K7139 A-type test pieces in accordance with JIS K7152-1 at a mold temperature of 90°C. The test pieces were cut to produce test pieces for measuring the deflection temperature under load.

[0293] The load deformation temperature (unit: ° C.) of the test piece for measuring the load deformation temperature was measured under a load of 1.81 MPa in accordance with JIS K7191.

[0294] As an evaluation standard, it was determined that the higher the measured value, the better the heat resistance.

[0295] (3) Impact strength

[0296] The JIS K7139 A-type test piece formed in (2) was cut to produce a test piece for measuring Charpy impact strength.

[0297] The Charpy impact strength (unit: kJ / m) of the test piece for measuring the Charpy impact strength was measured at a temperature of 23°C in accordance with JIS K7111-1 / 1eA. 2 ).

[0298] As an evaluation standard, it was determined that the higher the measured value, the better the impact resistance.

[0299] (4) Tensile strength

[0300] The JIS K7139 A-type test piece molded in (2) was measured for tensile strength (unit: MPa) at a temperature of 23° C. and a tensile speed of 5 mm / min in accordance with JIS K7161-1.

[0301] As an evaluation standard, it was determined that the higher the measured value, the better the tensile strength.

[0302] (5) Fatigue resistance

[0303] The pellets of the resin compositions of the examples and comparative examples described below were pre-dried at 80°C for 2 hours and then supplied to a coaxial screw injection molding machine (model: IS-100GN, manufactured by TOSHIBA MACHINE) set at 220-320°C to mold JIS K7119 No. III test pieces at a mold temperature of 90°C.

[0304] For the JIS K7119 No. III test piece, a plane bending fatigue test was performed in accordance with JIS K7119 using a repeated vibration fatigue testing machine (model: B-70, manufactured by Toyo Seiki Seisaku-sho, Ltd.) at a temperature of 23°C, a repeated stress of 40 MPa, and a frequency of 30 Hz. The number of repetitions until the test piece broke was measured and evaluated according to the following evaluation criteria.

[0305] [Evaluation criteria]

[0306] ◎: The number of repetitions until the test piece breaks is 5.00 × 10 6 above

[0307] ○: The number of repetitions until the test piece breaks is 3.00 × 10 6 More than and less than 5.00×10 6

[0308] △: The number of repetitions until the test piece breaks is 1.00×10 6 More than and less than 3.00×10 6

[0309] ×: The number of repetitions until the test piece breaks is less than 1.00 × 10 6

[0310] (6) Hot water resistance

[0311] The JIS K7139 A-type test piece molded in (2) and the Charpy impact strength test piece prepared in (3) were subjected to a high pressure cooking test (PCT) for 350 hours at a temperature of 130°C, a humidity of 100% RH, and a water vapor pressure of 0.17 MPa·G.

[0312] The impact strength and tensile strength of the test piece after PCT were measured in the same manner as (3) and (4), and the measured values ​​were divided by the impact strength and tensile strength before PCT, respectively, as the retention rates of impact strength and tensile strength.

[0313] As the evaluation criteria, it was determined that the higher the retention rate, the better the hot water resistance.

[0314] (7) Amount of butadiene monomer dissolved from the molded article into hot water

[0315] The pellets of the resin compositions of the examples and comparative examples described below were pre-dried at 80°C for 2 hours and then supplied to a coaxial screw injection molding machine (model: IS-100GN, manufactured by TOSHIBA MACHINE) set at 220-320°C, and molded into flat plates (50 mm×90 mm×2 mm) at a mold temperature of 90°C.

[0316] Four of the above-mentioned plates (total surface area S: 3.82 dm 2 ), a butadiene monomer elution test from a molded body into hot water was conducted according to the following procedure.

[0317] [0] Pre-cleaning

[0318] The plate rinsed with tap water for 1 hour was immersed in hot water maintained at 85±2° C. for 24 hours, and then rinsed with tap water for another 1 hour.

[0319] [1] Immersion test

[0320] The plate pre-cleaned in [0] was placed in hot water (volume V: 0.76 dm 3 ) for 24 hours (first immersion). Replace with hot water and continue to immerse in hot water (V: 0.76 dm 3 ) for 24 hours (second immersion). Replace with hot water and continue to immerse in hot water (V: 0.76 dm 3 ) for 24 hours (third immersion). Replace with hot water and continue to immerse in hot water (V: 0.76 dm 3 ) for 72 hours (the fourth immersion). The same operation was repeated three times to replace the hot water and immerse in the hot water for 24 hours (the fifth to seventh immersions).

[0321] [2] Determination of the amount of butadiene monomer dissolved

[0322] The butadiene monomer concentration of the hot water obtained in the seventh immersion in the above [1] was measured using purge & trap GC / MS as the elution amount of butadiene monomer (unit: μg / L).

[0323] (Purge & Trap Device) Model: JHS-100, manufactured by Japan Analytical Industry Co., Ltd.

[0324] (Purge gas) Helium

[0325] (Collector) Trade name: TENAX, manufactured by GLSciences

[0326] (GC / MS device) Model: GC-17A / QP-5050A, manufactured by Shimadzu Corporation

[0327] (Column) Trade name: DB-1, manufactured by Agilent Technologies

[0328] (Carrier gas) Helium

[0329] (Internal standard substance) Toluene-d8

[0330] (8) Mold release

[0331] After pre-drying the pellets of the resin composition of the embodiments and comparative examples described later at 80°C for 2 hours, the pellets were supplied to a coaxial screw injection molding machine (model: IS-100GN, manufactured by TOSHIBA MACHINE) set at 220-320°C, and at a mold temperature of 90°C, flat plates (50 mm×90 mm×2 mm) were injection-molded 300 times continuously. The degree of adhesion of the molded pieces to the mold was evaluated according to the following evaluation criteria.

[0332] [Evaluation criteria]

[0333] ○: No adhesion of the molded sheet to the mold was observed

[0334] △: Almost no adhesion of the molded sheet to the mold was observed

[0335] (Examples 1 to 36, Comparative Examples 1 to 12)

[0336] As a melt kneading machine, a twin-screw extruder (model: ZSK-25, manufactured by COPERION) was used.

[0337] A first raw material supply port is provided on the upstream side along the direction of raw material flow, a first vacuum exhaust port is provided on the downstream side of the first raw material supply port, a second raw material supply port is provided on the downstream side of the first vacuum exhaust port, and a second vacuum exhaust port is provided on the downstream side of the second raw material supply port. A kneading section is provided between the first raw material supply port and the first vacuum exhaust port, and between a supply port after the second raw material supply port and the second vacuum exhaust port. The raw material at the second raw material supply port is supplied from the side opening port using a forced side feeder.

[0338] Using the twin-screw extruder set as described above, according to the composition and raw material supply position shown in Table 1, melt-kneading was performed under the kneading conditions of melt-kneading temperature of 250-320°C, screw speed of 160 rpm, discharge volume of 10 kg / hour, and vacuum degree of -0.09 MPa to obtain a pelletized resin composition. It should be noted that for the component recorded as "external run" as the raw material supply position, after the pelletized resin composition is obtained, it is blended with the component so that it is spread on the pellet surface.

[0339]

[0340]

[0341]

[0342]

[0343]

[0344] Industrial Applicability

[0345] The resin composition of the present invention is excellent in mechanical properties such as tensile strength, impact strength, and fatigue resistance, and can maintain these mechanical properties at a high level for a long time even in a hot water environment. Its molded body can be suitably used as mechanical parts or housings related to water supply and drainage.

[0346] The molded article composed of the resin composition of the present embodiment is suitable for use as mechanical parts and housings related to water supply and drainage, such as pump housings, valves, piping components, flanges, water meters, heat exchangers, water purifiers, water softeners, and shower heads. It is particularly suitable as mechanical parts and housings related to water supply and drainage that come into contact with drinking water.

Claims

1. A resin composition comprising: Polyphenylene ether resin (a) 20 mass% to 50 mass%; 0.1% to 9% by mass of a polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or anhydride thereof; Homopolystyrene (c) 15 to 50% by mass; 1% to 25% by mass of one or more selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), wherein the hydrogenated block copolymer (d-1) is obtained by hydrogenating at least a portion of a block copolymer comprising a polymer block X and a polymer block Y, wherein the polymer block X is mainly composed of a styrene-based compound and the polymer block Y is mainly composed of a conjugated diene compound; and 5 to 35% by mass of glass fibers (e) surface-treated with at least a silane coupling agent and an ether-based polyurethane.

2. The resin composition according to claim 1, wherein The resin composition comprises: 0.01% to 1% by mass of one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite.

3. The resin composition according to claim 1 or 2, wherein The resin composition is molded to obtain a surface area of ​​Sdm 2 The molded body is immersed in a liquid having a volume of Vdm maintained at a temperature of 85±2°C. 3 The immersion and replacement of hot water were repeated. The amount of butadiene monomer dissolved into the hot water was less than 0.13 μg / L during the 7th immersion. The S / V ratio was 5.0 dm -1 .

4. The resin composition according to claim 1 or 2, wherein The resin composition comprises: 1 to 10,000 ppm by mass of one or more compounds selected from the group consisting of fatty acids, fatty acid esters, fatty acid metal salts and fatty acid amides (g).

5. The resin composition according to claim 1 or 2, wherein In the resin composition formed by melt-kneading, the weight average molecular weight of the component (a) is 45,000 or more and 90,000 or less.

6. The resin composition according to claim 1 or 2, wherein The modification rate of the unsaturated carboxylic acid or its anhydride in the component (b) is 0.3 mass % or more and 1.5 mass % or less.

7. The resin composition according to claim 1 or 2, wherein The hydrogenation rate of the component (d-1) is 95% or more.

8. The resin composition according to claim 1 or 2, wherein The content of the component (d-1) is 1% by mass to 5% by mass, and the content of the component (d-2) is 5% by mass to 25% by mass, based on 100% by mass of the resin composition.

9. The resin composition according to claim 1 or 2, wherein The content of the component (e) is 10% by mass or more and 35% by mass or less relative to 100% by mass of the resin composition.

10. A molded body, characterized in that: The resin composition comprises the resin composition according to any one of claims 1 to 9.

11. A mechanical component and a housing, characterized in that: It consists of the molded body according to claim 10.

12. The mechanical component and housing according to claim 11, characterized in that: It is used in contact with drinking water.

13. A resin composition comprising: Polyphenylene ether resin (a) 20 to 50% by mass, Homopolystyrene (c) 15 to 50% by mass, Glass fiber (e) 5 to 35 mass%, and 0.01% to 1% by mass of one or more compounds (f) selected from the group consisting of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, aluminum hydroxide, aluminum silicate and hydrotalcite.

14. The resin composition according to claim 13, wherein The resin composition comprises: 1% to 25% by mass of one or more selected from the group consisting of a hydrogenated block copolymer (d-1) and a rubber-modified polystyrene (d-2), wherein the hydrogenated block copolymer (d-1) is obtained by hydrogenating at least a portion of a block copolymer comprising a polymer block X and a polymer block Y, wherein the polymer block X is mainly composed of a styrene-based compound and the polymer block Y is mainly composed of a conjugated diene compound.

15. The resin composition according to claim 13 or 14, wherein The resin composition comprises: Polyethylene (h) 0.1 to 5 mass %.

16. The resin composition according to claim 13 or 14, wherein The resin composition comprises: 1 to 10,000 ppm by mass of one or more compounds selected from the group consisting of fatty acids, fatty acid esters, fatty acid metal salts and fatty acid amides (g).

17. The resin composition according to claim 13 or 14, wherein The glass fiber (e) is a glass fiber surface-treated with at least a silane coupling agent, an ether polyurethane and / or an ester polyurethane.

18. The resin composition according to claim 13 or 14, wherein The resin composition comprises: 0.1 to 9% by mass of the polyphenylene ether resin (b) modified with an unsaturated carboxylic acid or anhydride thereof.

19. The resin composition according to claim 13 or 14, wherein In the resin composition formed by melt-kneading, the weight average molecular weight of the component (a) is 45,000 or more and 90,000 or less.

20. The resin composition according to claim 18, wherein The modification rate of the unsaturated carboxylic acid or its anhydride in the component (b) is 0.3 mass % or more and 1.5 mass % or less.

21. The resin composition according to claim 14, wherein The hydrogenation rate of the component (d-1) is 95% or more.

22. The resin composition according to claim 14, wherein The content of the component (d-1) is 1% by mass to 5% by mass, and the content of the component (d-2) is 5% by mass to 25% by mass, based on 100% by mass of the resin composition.

23. The resin composition according to claim 13 or 14, wherein The content of the component (e) is 10% by mass or more and 35% by mass or less relative to 100% by mass of the resin composition.

24. A molded body, characterized in that The resin composition comprises the resin composition according to any one of claims 13 to 23.

25. The molded article according to claim 24, wherein The molded body is immersed in a liquid having a volume of Vdm maintained at a temperature of 85±2°C. 3 The immersion and replacement of the hot water were repeated, and the amount of butadiene monomer eluted into the hot water during the seventh immersion was less than 0.13 μg / L, wherein the surface area of ​​the molded body is Sdm 2 , S / V ratio = 5.0dm -1 .

26. A mechanical component and a housing, characterized in that: It consists of the molded body according to claim 24 or 25.

27. The mechanical component and housing according to claim 26, characterized in that It is used in contact with drinking water.

Citation Information

Patent Citations

  • JP1975051197A

  • JP1977017880B2

  • Color separation filter

    JP1986070502A

  • Continuous casting method for thin-walled ingot

    JP1988056336A

  • Production of polyphenylene ether resin having excellent color tone

    JP1988152628A